2010
DOI: 10.1080/10683160802672613
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards sex offenders regarding competency, liability, voluntariness of offence, and disposal: the influence of being classified as having a learning disability

Abstract: The principal aim of this study was to investigate whether attitudes towards judicial competency, legal liability, voluntariness of offence and judicial disposal options were influenced by known classification of an offender as learning disabled compared to an offender with a suggested intellectual disability, but not formally classified. Subsidiary aims were to explore participant attitudes based upon group membership and parental status. The sample consisted of 101 participants (69 undergraduate nursing stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…They advocated for regular audits of these reports to identify gaps in knowledge and practice. Price‐Jones and Barrowcliff () concluded that a learning disability can influence perceptions and attributions regarding an individual's AC. They opined that the presence or suspicion of a learning disability should prompt an assessment of AC as opposed to leading to an assumption that one is not competent.…”
Section: Special Populationsmentioning
confidence: 99%
“…They advocated for regular audits of these reports to identify gaps in knowledge and practice. Price‐Jones and Barrowcliff () concluded that a learning disability can influence perceptions and attributions regarding an individual's AC. They opined that the presence or suspicion of a learning disability should prompt an assessment of AC as opposed to leading to an assumption that one is not competent.…”
Section: Special Populationsmentioning
confidence: 99%
“…If a third-party informant is told the purpose of the evaluation is to rule in (or out) ID, these negative and inaccurate stereotypes of individuals with ID may be mobilized. Furthering this notion, introduction of this label (i.e., ID) may result in third-party informants viewing the evaluee as less responsible, similar to participants in previous research (e.g., Najdowski et al, 2009;Price-Jones & Barrowcliff, 2010), than if this label were not introduced. Providing information about a potential ID diagnosis and the purpose of the inquiry (i.e., sentencing) may trigger these implicit stereotypes, thereby influencing reports of the evaluee's functional abilities in the direction of exaggerated impairments.…”
Section: Stereotypes Of Persons With Intellectual Disability and Of Cmentioning
confidence: 71%
“…As a result, let us look at the influence of the ID label in this context. Price-Jones and Barrowcliff (2010) found that hypothetical persons labeled "learning disabled" were rated less competent and less responsible for a hypothetical sexual offense than persons without such a label. Similarly, Najdowski, Bottoms, and Vargas (2009) found that a hypothetical juvenile labeled as "mild MR" was perceived as less deviant and less responsible than an identical individual with "average IQ."…”
Section: Stereotypes Of Persons With Intellectual Disability and Of Cmentioning
confidence: 98%